3D-printed PLA/HA composite structures as synthetic trabecular bone: A feasibility study using fused deposition modeling. (March 2020) - Wu, Dan; Spanou, Andrea; Diez-Escudero, Anna; Persson, Cecilia
Abstract: Additive manufacturing has significant advantages, in the biomedical field, allowing for customized medical products where complex architectures can be achieved directly. While additive manufacturing can be used to fabricate synthetic bone models, this approach is limited by the printing resolution, at the level of the trabecular bone architecture. Therefore, the aim of this study was to evaluate the possibilities of using fused deposition modeling (FDM) to this end. To better mimic real bone, both in terms of mechanical properties and biodegradability, a composite of degradable polymer, poly(lactic acid) (PLA), and hydroxyapatite (HA) was used as the filament. Three PLA/HA composite formulations with 5-10-15 wt% HA were evaluated, and scaled up human trabecular bone models were printed using these materials. Morphometric and mechanical properties of the printed models were evaluated by micro-computed tomography, compression and screw pull out tests. It was shown that the trabecular architecture could be reproduced with FDM and PLA by applying a scaling factor of 2–4. The incorporation of HA particles reduced the printing accuracy, with respect to morphology, but showed potential for enhancement of the mechanical properties. The scaled-up models displayed comparable, or slightly enhanced, strength compared to the commonly used polymeric foam synthetic bone models (i.e. Sawbones). Reproducing the trabecular morphology by 3D printed PLA/HA composites appears to be a promising strategy for synthetic bone models, when high printed resolution can be achieved.